Managing Employees in the Digital Era: Adaptation Strategies and Competency Development - Kania Laelawati; Yulianah, Yulianah (Sean Institute, 2025)
The development of digital technology has brought significant changes to the world of work, particularly in how companies manage human resources. This study aims to analyze employee adaptation and competency development strategies in the digital era to remain relevant and competitive. The research method used is a descriptive qualitative approach, reviewing literature and in-depth interviews with managers and employees at several digital-based companies. The results of this study indicate that employee management in the digital era requires an adaptation strategy that emphasizes competency development, both technical and soft skills. The application of technology in recruitment, training, performance management, and administration has been proven to increase organizational efficiency and effectiveness. However, the success of HR digitalization is greatly influenced by employee readiness to adapt, company support through reskilling and upskilling, and the creation of a flexible, collaborative work culture oriented towards continuous learning. Thus, companies that are able to integrate aspects of technology, organizational culture, and competency development will be better prepared to face the challenges and global competition in the digital era.